Parenting with love and logic : teaching children responsibility - Cline, Foster (Piñon Press, 2006)
If you want to raise kids that who are self-confident, motivated, and ready for the real world, take advantage of the win-win approach to parenting. Your kids will win because they'll learn responsibility and the logic of life by solving their own problems. And you'll win because you'll establish healthy control -- without resorting to anger, threats, nagging, or exhausting power struggles.